Direct detection of DNA using electrical double layer gated high electron mobility transistor in high ionic strength solution with high sensitivity and specificity - Chen, Yen-Wen; Tai, Tse-Yu; Hsu, Chen-Pin; Sarangadharan, Indu; Pulikkathodi, Anil Kumar; Wang, Hsin-Li; Sukesan, Revathi; Lee, Geng-Yen; Chyi, Jen-Inn; Chen, Chih-Chen; Lee, Gwo-Bin; Wang, Yu-Lin (Sensors and actuators. B, Chemical, 2018)
•Electrical double layer (EDL) gated AlGaN/GaN HEMT has been used as DNA sensor for rapid DNA detection.•High sensitivity and selectivity is achieved; direct testing in physiological salt concentration.•Very low detection limit of 1 fM target DNA.•Selectivity elucidated for 6-,2-,1-base mismatch DNA.•Potential candidate for rapid DNA sensing in point of care diagnostics. In this research, we have realized an electrical double layer (EDL) gated high electron mobility transistor (HEMT) as DNA sensor. The sensing area on the gate electrode which is separated from the transistor channel is immobilized with probe DNA to capture target DNA from physiological salt environment. The detection limit of the sensor can be as low as 1 fM with very high sensitivity. The specificity of the DNA sensor is also demonstrated by controlling the hybridization temperature. By choosing the hybridization temperature slightly lower than the melting temperature of the well-matched sequence, the binding ratio can be controlled between the fully-matched and mismatched one. The sensor has demonstrated specificity, with the ability to achieve single base mismatch resolution. The sensor has the potential for rapid DNA sensing applications in cells, biomarkers and viruses.